Recording Temperature with Magnetic Supraparticles. Issue 31 (30th June 2022) - Reichstein, Jakob; Müssig, Stephan; Bauer, Hannes; Wintzheimer, Susanne; Mandel, Karl
Abstract: Small‐sized temperature indicator additives autonomously record temperature events via a gradual irreversible signal change. This permits, for instance, the indication of possible cold‐chain breaches or failure of electronics but also curing of glues. Thus, information about the materials' thermal history can be obtained upon signal detection at every point of interest. In this work, maximum‐temperature indicators with magnetic readout based on micrometer‐sized supraparticles (SPs) are introduced. The magnetic signal transduction is, by nature, independent of the materials' optical properties. This facilitates the determination of valuable temperature information from the inside, that is, the bulk, even of dark and opaque macroscopic objects, which might differ from their surface. Compared to state‐of‐the‐art optical temperature indicators, complementary magnetic readout characteristics ultimately expand their applicability. The conceptualized SPs are hierarchically structured assemblies of environmentally friendly, inexpensive iron oxide nanoparticles and thermoplastic polymer. Irreversible structural changes, induced by polymer softening, yield magnetic interaction changes within and between the hierarchic sub‐structures, which are distinguishable and define the temperature indication mechanism. The fundamental understanding of the SPs' working principle enables customization of the particles' working range, response time, and sensitivity, using a toolbox‐like manufacturing approach. The magnetic signal change is detected self‐referenced, fast, and contactless. Abstract : Temperature is one of the most important external influences for materials. In this work, the design, working principle, and tunability of temperature‐indicator supraparticles are presented. These supraparticles can record and memorize thermal influences up to 170 °C with a spectral magnetic readout. The magnetic signals are independent of optical constraints and can thus be utilized to obtain information from within dark, solid objects.